1991
DOI: 10.1002/ajmg.1320390323
|View full text |Cite
|
Sign up to set email alerts
|

The Noonan‐CFC controversy

Abstract: The Noonan syndrome and the cardio-faciocutaneous (CFC) syndrome have been described as phenotypically and genetically distinct entities. However, the resemblance between them led some authors to question the validity of this separation. We review available clinical evidence to support the opposite view, namely, that the Noonan and CFC syndromes are indeed distinct and separate conditions, both falling within the broad and causally heterogeneous spectrum of the Noonan/congenital lymphedema phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
(10 reference statements)
0
36
0
1
Order By: Relevance
“…16 Because of the overlapping clinical features there is an ongoing discussion whether CFC syndrome and NS are allelic, or whether CFC is a contiguous gene syndrome. 17,18 Although two patients with CFC were reported to have an interstitial deletion of 12q21-22, 19,20 no deletions could be found in a further seven CFC patients investigated by Zollino et al, 21 using the same probe employed by Rauen et al 19 Familial occurrence has been reported in two families. 22,23 In a family with both CFC and NS, Schollen et al 24 most recently identified a mutation in the PTPN11 gene.…”
Section: Noonan-ptpn11 L Musante Et Al 204mentioning
confidence: 95%
“…16 Because of the overlapping clinical features there is an ongoing discussion whether CFC syndrome and NS are allelic, or whether CFC is a contiguous gene syndrome. 17,18 Although two patients with CFC were reported to have an interstitial deletion of 12q21-22, 19,20 no deletions could be found in a further seven CFC patients investigated by Zollino et al, 21 using the same probe employed by Rauen et al 19 Familial occurrence has been reported in two families. 22,23 In a family with both CFC and NS, Schollen et al 24 most recently identified a mutation in the PTPN11 gene.…”
Section: Noonan-ptpn11 L Musante Et Al 204mentioning
confidence: 95%
“…5 In 2001, PTPN11 was found to be one of the causal genes of NS, and it was possible to demonstrate that well-characterized individuals with CFC did not have a mutation in PTPN11. [6][7][8] Furthermore, individuals with CFC did not carry mutations in the HRAS gene, which causes CS, another phenotypically similar condition.…”
Section: Neurologicmentioning
confidence: 99%
“…CFCS has a considerable clinical overlap with NS, and 'borderline' cases are commonly observed, which justified the long debated question of whether it was a separate nosologic entity or an extreme phenotype/ variant of NS [Fryer et al, 1991;Neri et al, 1991;Wieczorek et al, 1997].…”
Section: Cardiofaciocutaneous Syndromementioning
confidence: 99%